Cassava for the future: embryogenic liquid cultures suitable for new biotech techniques - Dedičová, Beata; Becerra Lopez Lavalle, Luis Augusto (Informa UK Limited, 2024)
Cassava, a crop of importance for subsistence farming in Africa, Asia, and Latin America, has the potential to benefit from global economic integration as a versatile industrial resource. Enhancing cassava productivity is not just a matter of agricultural competitiveness but a crucial step toward ensuring many communities' food security and livelihoods. Given its high performance in marginal environments, where climate change poses threats, ensuring food security and livelihoods relies on rapidly adapting cassava. This study aimed to develop a protocol that swiftly transitions cassava embryogenic short-period liquid suspension cultures, facilitating the regeneration of genetically stable